Faktor Berpengaruh pada Ketimpangan Distribusi Pendapatan Enam Provinsi di Pulau Jawa - Daivy Olliffiana; Rifki Khoirudin (BALANCE: Economic, Business, Management and Accounting Journal, 2022)
Development aims to improve the welfare of the people. To improve welfare, it requires economic growth that is quitte high, stable and equiable in income. High enough economic growth must be balanced with equity, so as not to create ineqalty. Growth is not a goal, but only a tool as a process to reduce proverty and redurce inequality in income distribution. Hence the reduction of inequality ofincome distribution is the essence of development results can be enjoyed fairly and equitably by all people, the problemof unequal income distribution will not arise. If the economic proformance is betteror is experiencing progress, then all people must also feel the impact of this progress in the form of an increase in the level of income. Because the distribution of income is very useful  in increasing economic growth and development,it is important for us to know whar factor affect in the inequality of income didtribution in Java. This variables used are econoc growth, provincial minium wages , open employment rate, ddegree of fiscal decentralization and growth in the human development index with multiple regression analysis for 2014-2019. The results showed that the only variables affecting income inequality were the provincial minimum wage and the open unemployment rate. The open unemployment rate variable has a coefficient value of -0.0502438. This means that when the exchange rate increases by Rp.1, income inequality will decrease by 0.0502438%. The open unemployment rate variable has a coefficient value of 0.0056812. This means that when the open unemployment rate increases by one percent, income inequality will increase by 0.0056812%. Meanwhile, economic growth, the degree of fiscal decentralization and the human development index have no effect on income inequality